show that a^x + a^(-x) is an even function ?
bhaveshvk18:
.....
Answers
Answered by
6
As we know ,
Functions are even or odd..
Here The L' Hospital rule can't be applied
F(x) =a^x a^-x
Then f(x)=
![{a}^{ - x} + {a}^{ - ( - x)} \\ \\ = {a }^{ - x} + {a}^{x} \\ \\ = f(x) {a}^{ - x} + {a}^{ - ( - x)} \\ \\ = {a }^{ - x} + {a}^{x} \\ \\ = f(x)](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B+-+x%7D+%2B+%7Ba%7D%5E%7B+-+%28+-+x%29%7D+%5C%5C+%5C%5C+%3D+%7Ba+%7D%5E%7B+-+x%7D+%2B+%7Ba%7D%5E%7Bx%7D+%5C%5C+%5C%5C+%3D+f%28x%29)
Hence f(x) is an Even function.
Functions are even or odd..
Here The L' Hospital rule can't be applied
Answered by
0
Heya _____
Que ____ show that a^x + a^(-x) is an even function ____
Answer is as given ______
f(x) = a^x + a^(-x)
a^-x + a-(-x)
a^-x + a^x
f(x)
So... it is an even function...
Thank you
Que ____ show that a^x + a^(-x) is an even function ____
Answer is as given ______
f(x) = a^x + a^(-x)
a^-x + a-(-x)
a^-x + a^x
f(x)
So... it is an even function...
Thank you
Similar questions